Spontaneous Regression of Palmar Warts after Suffering from Diffuse Contact Dermatitis against Alkyl Bromide - Gyohei Egawa; Tetsuya Honda; Kenji Kabashima (Karger Publishers, 2021)
Contact immunotherapy with several sensitizing chemicals such as diphenylcyclopropenone (DPCP) or squaric acid dibutyl ester (SADBE) have been used for the treatment of recalcitrant or multiple warts. Here, we report a case of multiple verrucae vulgaris (VV) on the palm which spontaneously resolved after the development of systemic contact dermatitis against alkyl bromide. We considered that our case accidentally mimics contact immunotherapy against multiple VV. VV sometimes regress spontaneously, which may be triggered by accidental contact dermatitis, as shown in our case.